HUBUNGAN KELENTUKAN OTOT PUNGGUNG DAN KOORDINASI MATA TANGAN TERHADAP AKURASI SMASH TIM BOLA VOLI PUTRA KECAMATAN RETEH - oktaviani, Ade irma; Saripin, Saripin; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of the research is the find out the relation between the back muscles stretch power with smash accuration hand eye,the relationship of back muscle formation and eye coorcination to the smash accuracy of the volleyball team boys districts reteh. The problem in this research is still a lot of players who fail in doing smash so that balls are struck out and concerning net.this study aims whether there is the relationship of back muscle formation and hand eye coordination to the smash accuracy of the vollyball team boys districts reteh. Sampling technique is the whole population (total sampling).the sample in this study is a team vollyball boys subdistrict reteh which amounted to twelve people, this test uses a type of correlation research,then test the data using the test of normality test, product test correlation moment, normalization test variables X₁ L₀maks (0,127) <Ltabel (0,242), normalization test variables X₂ L₀maks (0,145) < Ltabel(0,242), and normalization test variables Y L₀maks (0,214) <Ltabel (0,242). In other words normal data rates and research conclusions show where there is a relationship between the relationship of back muscle formation and hand eye coordination to the smash accuracy. Where large coosfesien correlation when viewed from the level of relationship( interpretation ),value r is to have a low level of relationships with a value interrations r 0,773,0,862 dan 0,710.Key Word : Back Muscle Formation And Hand Eye Coordination With Smash Accuracy.